Achievement of The Target Market Through Business Model Canvas in Small and Medium Enterprises (Smes) - Onan M Siregar; Selwendri Selwendri (Mahesa Research Center, 2020)
As a SME industry many challenges faced by entrepreneurs in central SMEs Pasar Bengkel to remain able to survive. The construction of the Medan - Tebing Tinggi toll road becomes a challenge for SMEs Pasar Bengkel entrepreneurs to remain able to survive in the business souvenirs typical Market Bengkel in Serdang Bedagai regency. For that apply the Business Canvas Model as one of the solutions for SMEs to be able to survive in reaching the target market. This study aims to support the model of Small and Medium Enterprises (SMEs), using a canvas model developed by Alexander Osterwalder. Based on the variables raised in this study and hypothesis model, this research includes descriptive research. Based on the nine blocks as the tools used in the customer segment is the customer that must be managed is the customer who accidentally came to shop, the value proposition of selling quality products in mass production that can be sold or deposited to other business actors. Marketing channels using social media and other promotional tools. Customer relationships with respect to hospitality, display products and provide food processing information to customers. In revenue streams using business to business activities; mass sales and do mouth to mouth marketing strategies. The main resources use various sources such as raw materials, equipment and technology utilization. Key activities that social media management can take and management of production and materials. Partnership is done to farmers and government. Pay attention to the cost structure of product processing, wages, packaging and equipment maintenance.